2019
DOI: 10.3389/fphar.2019.01192
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Renal Diseases: New and Old Players

Abstract: Inflammation, a process intimately linked to renal disease, can be defined as a complex network of interactions between renal parenchymal cells and resident immune cells, such as macrophages and dendritic cells, coupled with recruitment of circulating monocytes, lymphocytes, and neutrophils. Once stimulated, these cells activate specialized structures such as Toll-like receptor and Nod-like receptor (NLR). By detecting danger-associated molecules, these receptors can set in motion major innate immunity pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
177
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(181 citation statements)
references
References 256 publications
(282 reference statements)
3
177
0
1
Order By: Relevance
“…However, persistent inflammation promotes the synthesis of fibrogenic factors, thus leading to renal fibrosis (Xiao et al, 2014). Inflammatory cytokines, such as tumor necrosis factor-a (TNF-a), interleukin-1b (IL-1b), and IL-6, can directly mediate renal fibrosis through inflammatory infiltration, fibroblast activation and synthesis and degradation of ECM (Andrade et al, 2019;Gorjipour et al, 2019;Shrikant, 2019). Our results showed that NE-THCQ inhibited inflammatory infiltration in H&E staining analysis and reduced the levels of serum IL-1b and IL-6 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, persistent inflammation promotes the synthesis of fibrogenic factors, thus leading to renal fibrosis (Xiao et al, 2014). Inflammatory cytokines, such as tumor necrosis factor-a (TNF-a), interleukin-1b (IL-1b), and IL-6, can directly mediate renal fibrosis through inflammatory infiltration, fibroblast activation and synthesis and degradation of ECM (Andrade et al, 2019;Gorjipour et al, 2019;Shrikant, 2019). Our results showed that NE-THCQ inhibited inflammatory infiltration in H&E staining analysis and reduced the levels of serum IL-1b and IL-6 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The common causes for AKI include renal ischemia/reperfusion injury, systemic inflammatory processes/sepsis, hemodynamic impairment, and nephrotoxicity [7]. Among them, inflammation plays a critical role, and several experimental studies have demonstrated an important contribution of intra-renal and systemic inflammation in promoting parenchymal injury, repair, and fibrosis of the kidney [8][9][10]. Growing attention has been focused on C-reactive protein (CRP), a simply detectable inflammation biomarker, as a possible predictor of AKI and it has been recently recognized that CRP actively contributes in the pathogenesis and progression of AKI, by exacerbating local inflammation, impairing the proliferation of damaged tubular epithelial cells, and promoting the fibrosis of injured renal tissue [11][12][13][14][15].…”
mentioning
confidence: 99%
“…Observations made in culture cells in vitro, experimental animals in vivo, and kidney tissue from CSFs suggest that CaOx crystals can adhere to tubular epithelial cells, become transcytosed to the renal interstitium, and undergo dissolution within cells [8,11,12,[25][26][27]. The kidney harbors a variety of resident immune cells including macrophages and lymphocytes [28]. CaOx crystal deposition can activate renal immune cells to increase release of chemokines and pro-in ammatory cytokines, which in turn can recruit additional in ammatory cells including monocytes and neutrophils to the site [11,12,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The kidney harbors a variety of resident immune cells including macrophages and lymphocytes [28]. CaOx crystal deposition can activate renal immune cells to increase release of chemokines and pro-in ammatory cytokines, which in turn can recruit additional in ammatory cells including monocytes and neutrophils to the site [11,12,28,29]. EVs secreted by these immune cells can serve as a biomarker of their presence and activation, and may also serve signaling functions in vivo, including antigen presentation, immune suppression, and tissue remodeling [30].…”
Section: Discussionmentioning
confidence: 99%